(untitled) (Medical Forum Monthly, 2024)
Objectives: To analyze cadaveric based data of weight of heart, diameter and thickness of the walls of aorta in our population Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted at the Department of Anatomy and Pathology, Dow Medical College, DUHS, Karachi from 2008 – 2012. Materials and Methods: The hearts of one hundred cadavers (both male and female) were obtained from the morgue of Civil Hospital and other morgues of the Karachi. The hearts were removed in the usual necropsy procedure. Male and female cadaveric hearts were divided into six groups which were constituted ranging in age from 20 to 79 years i.e. Group A:20-29 (Vicenarian group), Group B: 30-39 (Tricenarian group), Group C: 40-49 (Quadrangarian group),Group D: 50-59(Quinquagenarian group), Group E: 60-69 (Sexagenarian group) and Group F: 70-79 (Septuagenarian group).Young and otherwise healthy individuals (died due to road traffic accident, Gunshot injury, Suicide or Homicide) were included in the study. The cadaver whose cause of death was known to be cardiac was not included in the study. Results: The mean weight of the heart is 286.14 grams ± 3.23 and between male and female the P-value is(P<0.00) which is significant. Average aortic diameters are 2.77 cm, ± .023 and between male and female the P-value is (P<0.01) which is significant. Average aortic wall thickness is 1.07mm ±0.16 with significant male and female p- value (P<0.01). Conclusion: Our study provided the measurement in the cadavers with regards to weight of heart and aortic diameter and the thickness of the wall of aorta. It is also concluded that results obtained show significant difference between male and female hearts with regards to these parameters.